Survival Benefit of Donation After Circulatory Death Kidney Transplantation in Children Compared With Remaining on the Waiting List for a Kidney Donated After Brain Death. Issue 3 (March 2022) - Kizilbash, Sarah J.; Evans, Michael D.; Chavers, Blanche M.
Abstract : Background: Kidneys donated after circulatory death (DCD) are increasingly being used for transplantation in adults to alleviate organ shortage. Pediatric data on survival benefits of DCD transplantation compared with remaining on the waitlist for a kidney donated after brain death (DBD) offer are lacking. Methods: We used Scientific Registry of Transplant Recipients to identify 285 pediatric (<18 y) DCD kidney transplants performed between 1987 and 2017. Propensity score matching was used to create a comparison group of 1132 DBD transplants. We used sequential Cox analysis to evaluate survival benefit of DCD transplantation versus remaining on the waitlist and Cox regression to evaluate patient and graft survival. Results: DCD transplantation was associated with a higher incidence of delayed graft function (adjusted odds ratio: 3.0; P < 0.001). The risks of graft failure (adjusted hazard ratio [aHR], 0.89; P = 0.46) and death (aHR, 1.2; P = 0.67) were similar between DCD and DBD recipients. We found a significant survival benefit of DCD transplantation compared with remaining on the waitlist awaiting a DBD kidney (aHR, 0.44; P = 0.03). Conclusions: Despite a higher incidence of delayed graft function, long-term patient and graft survival are similar between pediatric DCD and DBD kidney transplant recipients. DCD transplantation in children is associated with a survival benefit, despite pediatric priority for organ allocation, compared with remaining on the waitlist.